Improvement of efficiency of investment projects of the Republic of Kazakhstan by using of world experience - El’tinova, S. A. (Journal of Economic Research & Business Administration, 2015)
In present time of globalization any country tries to improve a social and economic condition of the population. For this purpose investment and innovative development by means of an exchange of technologies conducts to an important factor of economic growth. Now the condition of investment projects isn’t developed at the proper level. Presently for novelty, efficiency and positive influence of investment projects on economy are used a set of methods. We can see activity, the principles and methods in JSC “Samruk-Kazyna” works. The main principle of these works is – development of projects for improvement of quality of goods and services, and increase in economically effective projects.